The direct sound, the early reflections and the interrelation between their energy and the near and the remote acoustic fields / Tiesioginis garsas, ankstyvi atspindžiai ir jų energijos ryšys su artimu ir tolimu garso lauku - Stauskis, V. (Journal of Civil Engineering and Management, 1996)
The paper deals with the dependence of the near and remote acoustic field limits on the relationship between the direct sound and the first reflections' energy. A hall with the dimensions 13.6×10.7×7 m was chosen for the investigation. There were 120 semi-upholstered chairs in the hall, with no people. The selected investigation points were located 1 m and 11 m from the sound source. This choice was determined by the fact that in both cases the early sound reflections differ greatly in the delay time with respect to the direct sound and in their intensity.A question as to what duration of the direct sound should be taken in the measurements is of great importance. In his previous work the author has examined the relationship between the energies of the near and the remote acoustic fields as well as its dependece on the hall volume and absorption. It has been established that while seeking the ratio between the direct sound energy and the remaining energy it is better to assess the early sound reflections and not the diffusional acoustic field. In this paper, the duration of the direct sound was taken as 5 ms according to the recommendations found in the literature.It has been found experimentally that the duration of the direct sound is 1–1.7 ms and not 5 ms as recommended by the literature. There are no reflections in the time interval from 0 to 50 ms, only of the diffracted from the operator, microphone etc. The duration of the direct sound depends on the quality of the sound source itself, i.e. on the power of the shot etc. During the experiment the duration of the direct sound was established for each case separately.When the microphone is located at 1 m from the sound source, strong direct sound prevails. After 6.05 ms the first reflection from the floor reaches the listener. Its amplitude is lower by 4.2 dB than that of the direct sound. After 6.39 and 7.43 ms, two reflections arrive with amplitudes lower by 11.4 and 15.3 dB respectively than those of the direct sound. The next sound reflection from the ceiling reaches the listener as late as after 33.85 ms. In the time interval from 6.6 ms to 33.85 ms no reflections reach the listener. In this interval, the amplitude of the diffracted reflections affected by the interference is lower by as much as 20–55 dB than that of the direct sound. Such distribution of the reflection structure is only possible near the sound source. The reflection structure changes along with the increase in the distance from the source.Investigations show that in the case when the microphone is 1 m from the sound source the ratio between the direct sound energy and the first reflection energy is equal to 9.32, or 9.7 dB. The direct sound energy prevails and is bigger than the first reflection energy by a factor of 10. When the second reflection arrives after 6.39 ms, the direct sound energy is more than the sound energy of two reflections by a factor of 3.12 only, or 4.9 dB. The third reflection, which is less energetic, reduces this difference to 2.95, or to 4.7 dB. Further, to 33.85 ms there follows an area without sound reflections where only the diffracted sound is found. Due to this the energy ratio is only slightly reduced. Only after 43 ms the energy of the direct sound and the reflections of various intensity that have arrived earlier is equal to the direct sound energy. In this case the energies come to equilibrium in the performers' area after 45–50 ms. These results show that direct sound only prevails in the performers' zone in the course of the first 45–50 ms.Completely different results are obtained when the microphone is located 11 m from the sound source. In this case the ratio between the direct sound energy and the first reflection is as small as 1.18, or 0.7 dB, i.e. almost near one. With the second reflection, this ratio is equal to 0.8, or −1 dB, i.e. less than one. The ratio is markedly decreasing with the 3, 4, 5, 6 and 7 reflections. This is demonstrative of the fact that the influence of the first reflections over the equilibrium is much stronger at the point located relatively far from the sound source than near the source. The energy of only two reflections reaching the listener in 9.63 ms after the direct sound is sufficient to exceed the energy of the direct sound. When the microphone is 1 m from the sound source, this interval is roughly 45–50 ms.Article in Lithuanian.First Published Online: 26 Jul 2012